1970
DOI: 10.1063/1.1673792
|View full text |Cite
|
Sign up to set email alerts
|

Low-Frequency Modes in Molecular Crystals. IX. Methyl Torsions and Barriers to Internal Rotation of Some Three-Top Molecules

Abstract: Articles you may be interested inLow frequency modes in molecular crystals. XIX. Methyl torsions and barriers to internal rotation of some three top molecules with C 3 symmetry

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

1970
1970
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(13 citation statements)
references
References 50 publications
4
9
0
Order By: Relevance
“…All geometries were optimized using the B3LYP/cc-pVQZ method. The geometrical parameters, in general, are in good agreement with previous experimental 24,26,27 and theoretical results. 29,30 The IRC paths using the B3LYP/ cc-pVTZ method for the rotation motion were calculated by changing the dihedral angle d (H-C-N-lone pair) and the relative energy from the ground state structure (d = ± 60°), which are presented in Figure 3.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…All geometries were optimized using the B3LYP/cc-pVQZ method. The geometrical parameters, in general, are in good agreement with previous experimental 24,26,27 and theoretical results. 29,30 The IRC paths using the B3LYP/ cc-pVTZ method for the rotation motion were calculated by changing the dihedral angle d (H-C-N-lone pair) and the relative energy from the ground state structure (d = ± 60°), which are presented in Figure 3.…”
Section: Resultssupporting
confidence: 79%
“…24,25,27,28 The inclusion of core correlation is more important for the inversion barrier, as already discussed for the methylamine and dimethylamine. The calculated barrier height results for the torsion of one methyl group are consistent with the experimental and previous theoretical results.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…',2z and 3.38 lrcal/mol for solid (CH3j31'. 17 Since the values of many more barriers to rotation about the 1 ' 4 bond arc necessary before the nature of the substituent effects can be reasonably predicated, it was decided to record the far-infrared spectra of the series CH31'CI2, CH31'OClz, CHJ'OCIF', CH31'OI',, and CHsl'SCIz for the purpose of determining the frequencies of the torsional oscillations. Raman spectra of the c-orrcspondirig cwmpourids in the solid state were also recorded when feasible.…”
Section: Introductionmentioning
confidence: 99%
“…CH3 Torsions Torsional vibrations of methyl groups have been observed over a wide range of frequencies (270 to 100 cm-') in a variety of compounds (18,19). For the CH3AsX2 molecules (4) it was concluded that the torsions should lie in the range 185-135 cm-', but a definite assignment was only made in one case, namely 134 cm-' for CH,AsBr,.…”
Section: As-i Stretchingmentioning
confidence: 99%